The Contribution of Cash Receipts Accounting Information Systems in Strengthening Internal Control (Study on PT. KLN) - Duwi Rahayu; Herman Ernandi; Muhammad Irawan Saputra (IECON: International Economics and Business Conference, 2025)
This research examines how the cash receipts accounting information system contributes to strengthening internal controls at PT KLN, while evaluating the consistency of the company's practices with accounting theory and internal control standards. The study aims to provide insights for assessing and proposing enhancements to the system. Using a qualitative approach, data was gathered through interviews, documentation reviews, and observations. Technique triangulation was applied to ensure data validity, and analysis was conducted through data reduction, presentation, and conclusion formulation. The findings indicate that PT KLN's cash receipts accounting information system has not reached optimal performance, primarily due to the absence of a well-defined process flow diagram. Furthermore, internal control weaknesses persist, especially in the organizational structure, where a disconnect between administrative and financial roles hinders efficiency and accountability, necessitating corrective measures.